The Oxford Handbook of Cognitive Literary Studies: An exploration of arguments - Koneczniak, Grzegorz (Theoria et Historia Scientiarum, 2016)
In the review, I examine the Oxford Handbook of Cognitive Literary Studies, a volume edited by Lisa Zunshine (2015), from the perspective of selected arguments found in the essays.